Prevalensi dan Gambaran Klinis Skabies pada Santriwati Pondok Pesantren Darul Istiqamah Manado Tahun 2024 - Ramdani, Rezki A.; Wahongan, Greta J. P.; Pijoh, Victor D. (Medical Scope Journal, 2025)
Abstract: Scabies is an environmentally transmitted skin disease that remains a significant health issue in Indonesia, including in Islamic boarding schools. This study aimed to determine the prevalence and clinical features of scabies among female students at Darul Istiqamah Islamic Boarding School, Manado, in 2024. This was a descriptive study with a cross-sectional design. Samples included all female students that met the inclusion criteria. Data were collected through interview, clinical examination, and skin scraping for microscopic identification of Sarcoptes scabiei mites. A scabies diagnosis was established if at least two of the four cardinal signs of scabies were present. The results showed that there were 55 female students as subjects; 27.3% showed clinical features of scabies. The most common cardinal signs were group itching complaints (60%) and nocturnal pruritus (36.4%). In conclusion, the prevalence of scabies among female students at Darul Istiqamah Islamic Boarding School is relatively high compared to the national average. Environmental factors and personal hygiene play crucial roles in the spread of this disease. Preventive measures such as education and improved environmental hygiene are needed to reduce the transmission of scabies in boarding schools. Keywords: prevalence of scabies; cardinal signs; Islamic boarding school; Sarcoptes scabiei Abstrak: Skabies merupakan penyakit kulit menular berbasis lingkungan yang masih menjadi masalah kesehatan di Indonesia, termasuk di pesantren. Penelitian ini bertujuan untuk mengetahui prevalensi dan gambaran klinis skabies pada santriwati Pondok Pesantren Darul Istiqamah Manado tahun 2024. Penelitian ini menggunakan metode deskriptif dengan desain potong lintang. Sampel penelitian terdiri dari seluruh santriwati (n=55) yang memenuhi kriteria inklusi. Data dikumpulkan melalui anamnesis, pemeriksaan klinis, dan pengambilan sampel kerokan kulit untuk identifikasi tungau Sarcoptes scabiei. Diagnosis skabies ditegakkan jika ditemukan dua dari empat tanda kardinal skabies. Hasil penelitian mendapatkan 55 santriwati sebagai subjek penelitian. Terdapat sebanyak 27,3% santriwati memiliki gambaran klinis skabies. Tanda kardinal paling banyak ditemukan ialah keluhan gatal kelompok (60%) dan pruritus nokturna (36,4%). Simpulan penelitian ini ialah prevalensi skabies pada santriwati Pondok Pesantren Darul Istiqamah tergolong tinggi dibandingkan angka nasional. Faktor lingkungan dan kebersihan pribadi berperan penting dalam penyebaran penyakit ini. Upaya preventif seperti edukasi dan peningkatan kebersihan lingkungan diperlukan untuk menekan penyebaran skabies di pesantren. Kata kunci: prevalensi skabies; tanda kardinal; pondok pesantren; Sarcoptes scabiei